Effect of X-ray irradiation on the biological parameters of Xestia c-nigrum - Chu, Shijiao; Liu, Bing; Li, Huan; Lu, Keke; Lu, Yanhui (Frontiers in Physiology, 2024)
The sterile insect technique (SIT) is widely used to control Lepidopteran pests by inducing inherited sterility. The noctuid moth Xestia c-nigrum is a polyphagous pest whose subterranean larvae severely injure cereals and some vegetables. The goals of this study were to assess the impact of Xray irradiation on the development and survival of X. c-nigrum and use the data to select suitable sterilizing doses for potential future use in pest management. Batches of male pupae were exposed to 0 (control), 10, 30, 50, 100, 200, 300, or 400 Gy of X-rays, approximately 24 hours before adult emergence. Exposure of late-stage pupae to 10~200 Gy of radiation had no significant effect on adult emergence, but all doses (10~400 Gy) reduced adult longevity, the number of spermatophores in mated females, and the number of eggs laid per female in the irradiated parental generation compared with the controls. Exposure to 10 and 30 Gy had no significant effects in the F1 generation on (1) the rate of egg hatch, (2) the duration of larval or pupal development, or (3) adult longevity. However, exposure to 50 Gy reduced the rate of egg hatch in the F1 generation, and when male pupae were exposed to 100 Gy only 1% of the F1 eggs hatched. Also at 100 Gy, the developmental durations of larvae and pupae were significantly prolonged, and longevity of adult moths was reduced. There were no significant differences between the control group and any treatments in (1) the sex ratio of the F1 adults, (2) the duration of F1 pre-oviposition or oviposition periods, or (3) the number of eggs laid per F1 female. Our findings indicate that a dose of 100 Gy can effectively slow pest development and reduce larval survival in the F1 generation. In addition, F1 adults from lines treated with 100 Gy were able to mate and lay eggs, but all F2 eggs failed to hatch. Our results suggest that use of X-ray irradiation has potential to control this polyphagous pest at the regional level.